2007
DOI: 10.1111/j.1399-3062.2007.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia due to parvovirus B19 infection transmitted probably through hematopoietic stem cell transplantation

Abstract: Human parvovirus B19 is a very common infectious pathogen in humans. In healthy subjects, B19 infection is the cause of a self-limiting subclinical erythroid aplasia, followed by rash or arthralgia. In immunocompromised patients B19 can cause chronic anemia. This report presents the case of a 19-year-old male who developed severe anemia shortly after successful allogeneic hematopoietic stem cell transplantation. His marrow showed selective erythroid aplasia, and real-time polymerase chain reaction assay confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“… 33 Results from another case report also suggested that the occurrence of chronic pure red cell aplasia in a 19-year-old man was due to B19V transmitted through HSCT. 35 In the case described here, in which B19V was detected in donor and posttransplant recipient samples, despite extensive molecular investigation we were not able to prove transmission by allo-HSCT, because the obtained DNA sequences from patient 8 displayed a similar genotype 1a than its donor-derived sequences, but harbored different substrain polymorphisms. Molecular cloning also helped to rule out polyclonal infections and/or intergenotypic recombinant viruses, phenomena already described for B19V infections.…”
Section: Discussionmentioning
confidence: 55%
“… 33 Results from another case report also suggested that the occurrence of chronic pure red cell aplasia in a 19-year-old man was due to B19V transmitted through HSCT. 35 In the case described here, in which B19V was detected in donor and posttransplant recipient samples, despite extensive molecular investigation we were not able to prove transmission by allo-HSCT, because the obtained DNA sequences from patient 8 displayed a similar genotype 1a than its donor-derived sequences, but harbored different substrain polymorphisms. Molecular cloning also helped to rule out polyclonal infections and/or intergenotypic recombinant viruses, phenomena already described for B19V infections.…”
Section: Discussionmentioning
confidence: 55%
“…The time of the onset of PVB19 disease range from 0.03 to 96 months after HSCT. Rash and cytopenia are the main manifestations of PVB19 infection (26/32 cases) [12][13][14][15][16], followed by other symptoms including arthralgia, malaise, headache, myalgia, and pruritus [17][18][19][20][21][22][23][24]. Four of the 32 patients developed organ failure involving the heart, the lungs, or the kidneys [21,24],among which three patients also had cytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Parvovirus B19 (PVB19) is a single‐stranded DNA virus that commonly infects young children and is self‐limited in immunocompetent individuals with symptoms ranging from characteristic “slapped cheek” rash, viral exanthem, flu‐like symptoms, arthralgias, and occasional pure red cell aplasia 1,2 . PVB19 has a predilection for erythroid progenitor cells which can result in pure red cell aplasia, but PVB19 has also been associated with transient aplastic crisis 2‐4 . The exact mechanism of PVB19‐associated bone marrow failure is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that PVB19 has ability to replicate more efficiently in the relatively more hypoxic bone marrow microenvironment, leading to viral‐induced bone marrow suppression 3 . While mild infection occurs in normal hosts, PVB19 infection in immunocompromised hosts has been associated with hepatitis, pneumonitis, myocarditis, chronic pure red cell aplasia, and allograft dysfunction after solid organ transplant (SOT) and allogeneic hematopoietic stem cell transplantation (allo‐HSCT) 4‐15 …”
Section: Introductionmentioning
confidence: 99%